Influence of Thermodynamic, Material, and Bulk Properties on Electrical Resistivity of Particle Layers. Issue 4 (7th March 2014) - Pieloth, Damian; Wiggers, Helmut; Walzel, Peter
Abstract Although the influence of gas humidity and particle size distribution on dust resistivity is well known, the impact of thermic and electric balancing periods on the measurement of dust resistivity is less familiar. The dust resistivity of quartz glass (SiO2) and Al2O3 particle layers was measured and exhibits a non‐ohmic behavior as well as time dependence seen in a similar manner during electret formation. However, constant values of dust resistivity for the test dust were first measured after a rather long balancing period which cannot be explained in whole by adsorption and desorption kinetics of H2O into the particle layers. Rather, it could be presumed that the thermic and electric balancing periods overlap, whereas the electric balancing periods take a much longer time.